Ni2P/graphitic carbon nanostructure electrode with superior electrochemical performance. (1st May 2020) - Kim, Yo-Seob; Kim, Min-Cheol; Moon, Sang-Hyun; Kim, Hyeona; Park, Kyung-Won
Abstract: Because of their high theoretical specific capacities, transition metal phosphides have been interested as promising anode candidates for lithium-ion batteries. However, high irreversible capacity reduction and pulverization of the transition metal phosphide structure caused by volumetric expansion during cycling obstruct the commercialization of transition metal phosphides as an anode for lithium-ion batteries. In this study, we fabricated a nanostructured electrode consisting of nano-sized nickel phosphide (Ni2 P) and high-crystalline carbon (Ni2 P/C) using a chemical vapor deposition method and phosphidation process. The improved capacity and rate cycling performance of Ni2 P/C, i.e. 324 mAh g −1 at 200 mA g −1 after 200 cycles and 135 mAh g −1 at 1600 mA g −1, might be attributed to the relief of volumetric expansion and prevention of pulverization caused by the surrounding graphitic carbon structure in the vicinity of Ni2 P nanophase. Graphical abstract: Image 1